Greater Monetary Policy Transparency for the G3 : Lessons From Full-Fledged Inflation Targeters - Stone, Mark (IMF Working Papers; Working Paper ;, 2003)
The experience of full-fledged inflation targeting (FFIT) countries is used here to shed light on the costs and benefits of greater monetary policy transparency for the G3. For the United States and the euro area, a hypothetical adoption of FFIT would incur a cost of less discretion while gaining the benefit of locking in a highly credible framework. The adoption of FFIT by Japan would create the risk of a further hit to credibility if policy was not able to end deflation. In practice, the G3 are already moving toward a new monetary regime that resembles FFIT in transparency, but not in accountability.